2011
DOI: 10.4061/2011/563657
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hypertension on Patients with Acute Coronary Syndromes

Abstract: Arterial chronic hypertension (HTN) is a well-known cardiovascular risk factor for development of atherosclerosis. In order to explain the relation between HTN and acute coronary syndromes the following factors should be considered: (1) risk factors are shared by the diseases, such as genetic risk, insulin resistance, sympathetic hyperactivity, and vasoactive substances (i.e., angiotensin II); (2) hypertension is associated with the development of atherosclerosis (which in turn contributes to progression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 60 publications
4
47
1
3
Order By: Relevance
“…Notably, the great majority of patients with hypertension were found with STEMI followed by NSTEMI. In general, the prevalence of hypertension rises progressively with age in both men and women and ac as strong risk factor for ACS [23]. A previous study revealed a 63.4% prevalence of hypertension among ACS patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the great majority of patients with hypertension were found with STEMI followed by NSTEMI. In general, the prevalence of hypertension rises progressively with age in both men and women and ac as strong risk factor for ACS [23]. A previous study revealed a 63.4% prevalence of hypertension among ACS patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in mice, aberrant D 3 receptor expression in heart and in peripheral vascular systems may increase intimal permeability, vascular remodeling, atherosclerosis formation, or the possibility of plaque rupture by interacting with renin, angiotensin II, insulin, endothelin, and cytokine vascular permeability factor/vascular endothelial growth factor. [33][34][35][36][37][38] Additionally, there are several blood coagulation pathways involving D 3 receptors systems, including the activation of platelet aggregation and the secretion of the procoagulant von Willebrand factor. 39,40 Hence, D 3 receptors blockade could also predispose the patient to the formation of acute thrombosis in stenotic coronary arteries, contributing to AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the prognostic role of a pre-existing hypertensive state in ACS patients are contradictory and come mostly from old trials and registries, before the era of thrombolysis. 1 In patients with acute myocardial infarction (AMI), the prevalence of history of HTN varies from 31 to 59%. 2,3 On the contrary, it is not clear whether previously known hypertensive patients have an increased rate of adverse outcomes after non-ST elevation AMI (NSTEMI).…”
Section: Introductionmentioning
confidence: 99%